Assessment of the iliolumbar artery: its structural variations and applied aspect - Upadhayay, Parul; Hansdak, Ranjeeta; Agarwal, Sneh (International Journal of Research in Medical Sciences, 2021)
Background: The Iliolumbar artery normally arises from the posterior division of Internal iliac artery. The main artery and its two branches supply the iliacus and lumbar region and other vital structures in that area. However, various studies conducted depict the differences in the pattern of its origin and course. Thus, the goal of this study was to discover the various origins of the iliolumbar artery, as well as its relationships with other surgically significant anatomical structures; the importance of which can prevent any intraoperative hemorrhages during surgery. Methods: The study was conducted in Department of Anatomy Lady Hardinge Medical College between 2019-2021. Pelvis of 12 formalin fixed adult cadavers (8 females, 4 males) were dissected to observe the iliolumbar artery. Its origin, caliber and course were measured using a digital vernier caliper. The relationship of iliolumbar artery was established with obturator nerve, lumbosacral trunk and sympathetic chain. Results: Iliolumbar artery was originating from trunk of internal iliac artery in 70.83% cases in which the mean distance of origin and mean caliber was more on right side. In the remaining 29.17% cases where the Iliolumbar artery was arising from posterior division of internal iliac artery, the mean distance of origin and mean caliber was higher on left side. The truncal origin of iliolumbar artery was predominant in females. Conclusions: The variant origin of the iliolumbar artery and its clinic-anatomical relationships have been highlighted to reduce iatrogenic artery trauma during surgery.